The Development of the Human Resources Management Units - Kulić, Radivoje N.; Đurić, Igor R. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The necessity of personnel management became clear in the second half of the 19th century - when its different organizational forms started taking shape. From then, until the mid-80s, the personnel function – personnel management – changes and enriches its contents in accordance with the new reflections on people management in enterprises and companies. During the 1990s, in North America and Europe, the concept of human resource management and „human resources“ as the organizational form of its implementation are increasingly promoted in some organizations. At the same time, personnel departments and the departments of human resources „coexist“ in contemporary practice, while in some socio-cultural settings, there is no basic difference between these two concepts and theoretical levels. Nevertheless, a part of the specialized literature in Europe and in our country, there is a prevailing assessment that the department for Human Resources and Educational Service is an optimal organizational framework for implementation of personnel management – human resources, including a comprehensive guidance on training and development of all categories of employees.
Keywords: training and development; HR development unit; human resources departments; personnel management